The thin film PVA - bromocresol green dosimeter - Dung, Nguyen Van (Communications in Physics, 2013)
The thin film PVA (polyvinyl alcohol) - bromocresol green ( 15mm) dosimeter was made and with the application of the radiation technology. It’s parameters before and after gamma irradiation have been studied using optical spectrometer UV-VIS JASCO-V-350 and film densitymeter X-Rite Model 301. Result shows that the wave of thin film is 625nm, the sensitivity of thin film dosimeter is 0.013x10-3Gy-1 in the range of dose from 1kGy to 140kGy. The dose response function of dosimeter was clearly described by the theory of energy transfer model